Psychological barrier and cross-firm return predictability - Huang, Shiyang; Lin, Tse-Chun; Xiang, Hong (Journal of Financial Economics, 2021)
We provide a psychological explanation for the delayed price response to news about economically linked firms. We show that the return predictability of economically linked firms depends on the nearness to the 52-week high stock price. The interaction between news about economically linked firms and the nearness to the 52-week high can partially explain the underreaction to news about customers, geographic neighbors, industry peers, or foreign industries. We also find that analysts react to news about economically linked firms but the 52-week high effect reduces such reactions, providing direct evidence that the 52-week high affects the belief-updating process.